Hybrid Wars Strategy of NATO Countries as a Challenge for the Russian Federation - Nikolaj A. Baranov; Pavel P. Popov (Евразийская интеграция: экономика, право, политика, 2019)
Modern technologies, changing a habitual picture of the world and perception of reality, lead to cardinal changes in all spheres of society activity, including military science. There are new forms and ways of conducting combat operations that led to forthcoming of hybrid wars based on diplomatic, economic, military and information infl uence. The article describes defi nitions of hybrid wars and infl uence on their carrying out such technologies as the posttruth and “fake news”. The analysis of the Hybrid Wars Strategy approved by the NATO countries and adopted as a basis for control of Russia and also the concept of hybrid threats as the tool used for causing damage to the state or the coalition of the states without direct or limited use of military force has been carried out. Forms and ways of control and practice of realization of NATO Hybrid Wars Strategy against Russia have been considered.